Time limits on welfare use under involuntary unemployment - Christian Holzner; Volker Meier; Martin Werding (Center for Economic Studies and ifo Institute (CESifo), 2004)
The impacts of introducing or tightening time limits on welfare use are studied in an efficiency wage model. Those losing access to regular benefits receive some smaller benefit, which can be interpreted as food stamps. Stricter time limits raise both employment and profits and generally reduce the tax rate. The impact on the net wage is ambiguous. Changes of utility levels of employed workers and recipients of regular social assistance have the same sign as the variation in the net wage. The utility differential between social assistance recipients and food stamp participants shrinks.
Keywords: J60; J41; H53; 330; welfare benefits; time limits; efficiency wages; Sozialhilfe; Dauer; Effizienzlohn; Unfreiwillige Arbeitslosigkeit; Theorie